Mesin Pengiris Tempe Semi Otomatis Jenis Disc Cutter Vertical - Hilda Porawati; Ari Kurniawan (LPPM Politeknik Jambi, 2021)
Rempeyek Ilham is one of the Micro, Small and Medium Enterprises (MSMEs) in Jambi City which is engaged in the production of tempeh peanut brittle. The increase in the capacity of the tempeh slices is done by making an automatic tempeh slicing machine using a vertical disc cutter. The slicing method is to use a crankshaft mechanism which produces a reciprocating motion with a 2-way movement direction, namely the transfersal direction and the longitudinal direction. The thickness of the wedge is regulated by a stopper with the help of a spring push mechanism. The results showed that the tempe cutting machine with a cutting time of 1 minute 37 seconds, the average number of slices obtained with a size of 2 mm was 83.8 slices and for sizes above 2 mm (2.1 mm-3 mm) as many as 68 slices, and the rest of the tempeh pieces are 5.6 cm long.